(untitled) (Federal University Gusau Faculty of Education Journal, 2025)
The paper examines stress management and coping mechanism through health education at tertiary level of education in Zamfara state, Nigeria. The aim of the paper is to identify the strategies, procedures for stress management and coping mechanisms through health education in Zamfara state. In order to achieve this aim therefore, the paper review related literature such as introduction that provide a brief caption of what the paper is all about, the concept of health education as a process of enlighten peoples about their health in physical, mental, emotional and psychological wellbeing through health advocacy, sensitization and awareness, stress and it types such as acute and chronic stress. Biological need for stress equilibrium, signs and causes of stress, stress management techniques and stress coping mechanisms as well as healthy ways to cope with stress, roles of health education in stress management were discussed. Meanwhile, the paper recommended some of the following suggestions, Health education should be given priority through enlightenment and advocacy on stress management strategies and coping mechanism as well as pros and cons involve towards mitigating self-care when dealing with difficult stress situations. Individuals should be enlightened through health education to developed and adopt the spirit of engaging in an exercise thereby securing at least hour and a quarter (1:15 minutes) per week could help to reduce the risk of early death, cardiovascular diseases, stroke and cancer.